Habilidades sociales y actitud emprendedora en estudiantes del quinto de secundaria de una institución educativa del distrito del Callao - Alanya Reque, Silvia Beatriz (2012)
The present study aimed to determine the relationship social skills and between entrepreneurship of students in a fifth of secondary school of Callao. The methodology was descriptive-correlational. The sample consisted of 151 students. The instrument used to measure the entrepreneurial attitude Profile Questionnaire was the entrepreneurial potential of Garcia (2001) adapted by Peralta (2010), and social skills scale was used Gismero social skills (2000). The results demonstrate a significant positive correlation between the low and entrepreneurial in its three dimensions: ability to perform capacity planning and ability to interact socially with social skills.